TLC densitometric method for screening of lycopsamine in comfrey root (Symphytum officinale L.) extracts using retrorsine as a reference compound - Janeš Damjan; Kreft Samo (Acta Pharmaceutica)
Due to severe toxicity of pyrrolizidine alkaloids, their quantification in medicinal products is very important. The idea of this research was to use retrorsine as a surrogate reference compound instead of lycopsamine reference or lycopsamine isolated from comfrey. A method for the analysis of lycopsamine in extracts of comfrey roots was developed and validated, employing thin layer chromatography, derivatisation with Dann-Mattocks reagent followed by densitometric analysis. The new method showed linearity within 0.70 to 7.0 μg of lycopsamine per application of 10 μL of a solution. It has also been proven to be specific and precise (repeatability RSD 2-4 % within the plate). The method was successfully employed for quantification of lycopsamine in comfrey root and comfrey root medicinal products such as ointments.